Factors that Influence the selection of Reservoir Construction Providers using the E-Purchasing Method via Electronic Catalog - Putra, Aditya; Biantoro, Agung Wahyudi (Universitas Ibn Khaldun Bogor, 2025)
The implementation of Electronic Catalog Purchasing in the Construction Sector for Reservoir Development carried out by the DKI Jakarta Provincial Water Resources Service is something new in Indonesia and includes the implementation/utilization of the Risk-Based Construction Sector Catalog, so catalog users need to have adequate technical understanding of the field and be able to mitigate risks. Apart from that, the product specifications and prices displayed by Business Actors are not yet final, therefore, at the purchasing stage a